Design, synthesis, anticancer activity and molecular docking studies of new benzimidazole derivatives bearing 1, 3, 4-oxadiazole moieties as potential thymidylate synthase inhibitors. (19th July 2022) - Almalki, Abdulraheem SA; Nazreen, Syed; Elbehairi, Serag Eldin I.; Asad, Mohammad; Shati, Ali A.; Alfaifi, Mohammad Y.; Alhadhrami, Abdulrahman; Elhenawy, Ahmed A.; Alorabi, Ali Q.; Asiri, Abdullah M.; Alam, Mohammad Mahboob
Abstract : Compounds 10 and 14 arrest the cell cycle at the G1 phase and induce apoptosis without any necrosis in MDA-MB-231 cells. Abstract : The present work describes the synthesis and anticancer activity of new benzimidazole derivatives bearing 1, 3, 4-oxadiazoles as thymidylate synthase inhibitors. The newly synthesized molecules were confirmed by NMR, mass, FT-IR and elemental analyses. From the anticancer activity results, compounds 10 and 14 showed higher sensitivity and better IC50 values in the range of 1.15–6.27 μM against lung A549, ovarian SKOV3 and breast MDA-MB 231 cancer cells in comparison to the standard drug 5-fluorouracil (IC50 : 10.65–15.48 μM). Moreover, these two compounds caused significant inhibition of the TS enzyme with IC50 values of 1.01 and 1.19 μM (more than 80% TS inhibition) compared to 5FU (IC50 : 1.91 μM). The mechanistic investigation of compounds 10 and 14 on cell cycle progression and apoptotic induction by flow cytometry showed that compounds 10 and 14 both arrest the cell cycle at the G1 phase in breast MDA-MB-231 cells, while in lung A549 and ovarian SKOV3 cells, compound 10 arrests the G2 phase, whereas compound 14 arrests the G1 and S phases. Furthermore, these compounds induce both early and late apoptosis without any necrosis in MDA-MB-231, SKOV3 and A549 cells. The docking study against the thymidylate synthase protein and ADMET analysis further supported the promising cytotoxicity results shown by these compounds. The present study strongly supports the anticancer activity of compounds 10 and 14 which could be considered as promising lead candidates for the development of TS inhibitors.